Estrutura da comunidade ictioplanctônica em um rio Neotropical: quais fatores podem modular essa estruturação? - Silva, Merieli de Melo da (2020)
Spatial heterogeneity results in dissimilarity in the composition of fish species with different life histories by influencing the availability and distribution of refuge, food and habitat for breeding. Understanding how this composition is organized along an environmental gradient is of paramount importance in order to protect the spawning sites and preserve the conditions favorable for the dispersion and growth of the larvae after the reproductive process. Thus, it was possible to verify the possible differences in the density of larvae and in the structure of the ichthyoplankton community between biotopes of a fluvial system, specifically intends to (i) answer whether the structure and attributes of the ichthyoplankton community, as well as that of parental reproductive guilds, differ between biotopes with different current speeds; (ii) to identify possible ontogenic variations in the occupation of different biotopes and (iii) to relate environmental factors to the occurrence and abundance of larvae among the biotopes. For this purpose, ichthyoplankton collections were performed in the lower region of the Ivinheima River, a floodplain of the upper Paraná River, during two reproductive periods (2010/2011 and 2011/2012) of the fish. In the river biotope, nine of the 19 long-distance migratory species recorded in the region were found in their early stages of development. Among these, Brycon orbignyanus, categorized as "endangered" and the species Pseudoplatystoma corruscans and Piaractus mesopotamicus as "almost threatened", emphasize the importance of maintaining busbar-free lotus environments for the reproductive success of reophilic species, as well as for migratory species of short distances, which also contributed to greater diversity in this biotope. Larvae in early development stages were recorded in the river, which indicates that the species use this biotope as a migratory route and also as a spawning area. Subsequent to spawning, through the current flow, the larvae develop and hatch, while they drift to places with low current speed to develop the larvae. In these places, here characterized as a transition area and pond, non-migratory species with external fertilization were the most abundant. Finally, the environmental factors had no detectable effects on the community structure, however it was observed that the larvae density showed a pattern of distribution among certain thresholds of the environmental variables. It is concluded that the hydrodynamic conditions of the river, especially the direction and speed of the water, influence the distribution patterns of the fish community with different reproductive strategies.